2012
DOI: 10.1111/j.1532-849x.2011.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crown Ferrule Heights and Dowel Material Selection on the Mechanical Behavior of Root‐Filled Teeth: A Finite Element Analysis

Abstract: Purpose: This study used the 3D finite element (FE) method to evaluate the mechanical behavior of a maxillary central incisor with three types of dowels with variable heights of the remaining crown structure, namely 0, 1, and 2 mm. Materials and Methods: Based on computed microtomography, nine models of a maxillary central incisor restored with complete ceramic crowns were obtained, with three ferrule heights (0, 1, and 2 mm) and three types of dowels (glass fiber = GFD; nickel‐chromium = NiCr; gold alloy = Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…38 The finite element mesh of each model was imported with a finite element software (Abaqus 6.10-EF1; Dassault Systèmes Simulus Co) to simulate a static occlusal loading of 180 N on the lingual surface of the incisal third of the tooth at 45 degrees in all models. 29 For the boundary condition, the nodes of the periodontal ligament were fixed in the 3 axes in the Cartesian plane (x, y, and z) assuming values of x=y=z=0 (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The finite element mesh of each model was imported with a finite element software (Abaqus 6.10-EF1; Dassault Systèmes Simulus Co) to simulate a static occlusal loading of 180 N on the lingual surface of the incisal third of the tooth at 45 degrees in all models. 29 For the boundary condition, the nodes of the periodontal ligament were fixed in the 3 axes in the Cartesian plane (x, y, and z) assuming values of x=y=z=0 (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…1). Regardless of the reconstructive technique of the internal radicular wall, a 50 mm thick cementation layer 29 was simulated in all models, with the exception of the GW model, in which the total thickness of the weakened area was simulated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some authors, a high number of vertical fractures are observed in roots with metallic posts with a high elastic modulus that distribute and concentrate stress in the apical third of the root 11,20,28 . Thus, the use of intra-radicular posts with an elastic modulus similar to dentin, such as glass fiber posts, promotes better stress distribution in the remaining dental structure and along the cementation interface 7,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a cervical ferrule positively affects the stress distribution pattern by reducing stress concentration on the root and risk of tooth fracture. Finite element analysis shows that the ferrule effect attenuates stress intensity on the root when either metal or fiber posts are used [12][13][14][15] . Previous studies also did not find a difference in fracture resistance between teeth restored with crowns and cast and post cores or fiber posts when a ferrule was present 13,16,17 .…”
Section: Discussionmentioning
confidence: 99%